Korelasi Kebebasan Finansial Terhadap Loyalitas Antarpelajar Di SMA Trensains Muhammadiyah Sragen - Danar Andria Wirawan; Barir Faqih (SMA Trensains Muhammadiyah Sragen, 2022)
Loyalty is one of the social attitudes favored by everyone. An attitude that creates a pleasant and supportive atmosphere, and maintains harmony in life for a longer time. Loyalty itself is influenced by several factors, one of which is satisfaction. From ancient times until now, the financial condition is very influential on one's satisfaction. Based on this, the researchers assume that financial condition indirectly affects one's loyalty. The purpose of this study was to determine the correlation between financial freedom and loyalty among students. This type of research is descriptive and quantitative, with the focus of the description being financial freedom. The research was carried out at SMA Trensains Muhammadiyah Sragen. The research sample amounted to 74 students. The 74 samples will be asked to fill out a questionnaire that will be given to the sample. After obtaining the data from the questionnaire, will be tested the data with a parametric correlation test. From this study, it was found that students who have high financial freedom tend to have high inter-student loyalty as well. The results of the correlation test between the two variables indicate that there is a correlation with a value of 67,7%. Based on the questionnaire data and data testing, it can be concluded that there is a correlation between financial freedom and loyalty among students.